Hubungan Pemakaian Pantyliner, Obesitas Dan Perilaku Personal Hygiene Dengan Kejadian Keputihan Pada Remaja Di SMPN 1 Sandai Kabupaten Ketapang : The Relationship between Pantyliner Use, Obesity and Personal Hygiene Behavior with the Incidence of Vaginal Discharge in Adolescents at SMPN 1 Sandai Ketapang Regency - Nurhaliza (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Vaginal discharge is a clinical disorder that is often complained of by all women. Vaginal discharge or flour albus is a vaginal condition when it discharges fluid or mucus that resembles pus. The purpose of this study was to determine the relationship between pantyliner use, obesity, and personal hygiene behavior with the incidence of vaginal discharge in adolescents at SMPN 1 Sandai Ketapang Regency in 2021. This research is a quantitative type with an analytic nature. The research design used is a cross-sectional study. The population in this study for adolescents at SMPN 1 Sandai Ketapang Regency in 2021 was as many as 132 people. Sampling using a purposive sampling technique. So, the sample in this study was 99 respondents. The instrument used is a questionnaire. This study uses the chi-square test. Based on the results of the statistical test it is known that the pantyliner usage variable has a p-value = 0,004; with an OR value = 5,574; an Obesity variable with a p-value = 0,016 with an OR value = 3.585, and a personal hygiene behavior variable with a p-value = 0,003 with an OR = 3,882. So, the conclusion is that there is a relationship between the use of pantyliners, obesity, and personal hygiene behavior with the incidence of vaginal discharge in adolescents at SMPN 1 Sandai Ketapang Regency in 2021. Suggestions for Public Health Center to be able to provide reproductive health education to adolescent girls at school.  Methods: This study uses a cross-sectional with a quantitative type of research conducted on adolescents at SMPN 1 SANDAI. Research subjects were selected by purposive sampling method. Results: This study used the chi-square test. Based on the result of the statistical test, it was found that the use of pantyliner variables had a p-value = 0,004; OR = 5,574; obesity had a p-value of 0,016 and OR = 3,585; and personal hygiene behavior had a p-value = 0,003 with OR = 3,882. So, in conclusion, there is a relationship between the use of pantyliners, obesity, and personal hygiene behavior with the incidence of vagial discharge in adolescents at SMPN 1 Sandai, Ketapang Regency in 2021.  Discussion: There is a relationship between the use of pantyliners, obesity, and personal hygiene behavior with the incidence of vaginal discharge in adolescents at SMPN 1 Sandai Ketapang Regency in 2021.